A PUBLIC SURVEY REGARDING CHILDHOOD LANGUAGE IMPAIRMENTS - Georgeta Zegan; Ecaterina Gabriela Totolan; Cristina Gena Dascalu; Loredana Golovcencu; Daniela Anistoroaei (Romanian Society of Oral Rehabilitation, 2019)
Aim of the study was to investigate the Romanian population regarding the awareness of childhood language impairment. Material and methods: 75 Romanian volunteers (37 male and 38 female) aged 18-78 randomly selected were surveyed through a questionnaire carried out by Working Group 3 of Cost Action IS1406, between March-May 2018. The questions were grouped in 5 sections: personal information, knowledge about childhood language impairment, management/ therapy/ intervention, the role of parents in intervention and improving the lives of these children. Multiple answers were analysed by the SPSS 16.0 package (SPSS Inc., Chicago, IL) for Windows. Results: 57.3% respondents knew the term childhood language impairment. 42.7% respondents heard about language therapy for children. 40% respondents believe that parents should engage in team work with the therapist. 77.3% of respondents believe that school education is the best ways to spread information about childhood language impairments. The correlations between answers and age groups, level of education, the economic status of the volunteers and the parents of the children under 18 have shown statistically significant differences (p<0.05). Conclusions: This survey has identified the status of the awareness of Romanian population regarding childhood language impairments and there was a gap between people who can recognize the child's language impairment, depending on socio-demographic characteristics.